E-SCRAPBOOK AS AN INNOVATION MEDIA FOR LEARNING THE HISTORY OF ISLAMIC CULTURE AT MI IN THE DIGITAL ERA - Dewi Mawardini, Intan; Chasanah, Iflahathul; Chasanah, Chasanah (Ibriez : Jurnal Kependidikan Dasar Islam Berbasis Sains, 2024)
The Islamic Cultural History subject taught at the Madrasah Ibtidaiyah level discusses the past. However, in fact, in delivering the material, most teachers find it difficult to illustrate, which ultimately results in students still not understanding the learning material. The limitations of existing learning media, the majority of which still depend on LKS books and packages, are considered not effective enough in accommodating students' needs in the digital era. Development and use of e-scrapbook media in the History of Islamic Culture subject at Madrasah Ibtidaiyah. Of course, the application of e-scrapbook media is very useful in overcoming problems that arise during the learning process. The output from using this e-scrapbook media, which has two functions at once, namely as a learning medium that can motivate students and also increase understanding of the subject History of Islamic Culture. The research method that the author uses in this article is library research. This data collection is of course the result of the author's analysis, identification and evaluation of existing research works to be adapted to the topic raised, namely the use of e-scrapbook media.